Tethering Complexes in the Arabidopsis Endomembrane System - Vukašinović, Nemanja; Žárský, Viktor (Frontiers in Cell and Developmental Biology, 2016)
Abstract Targeting of endomembrane transport containers is of the utmost importance for proper land plant growth and development. Given the immobility of plant cells, localized membrane vesicle secretion and recycling are amongst the main processes guiding proper cell, tissue and whole plant morphogenesis. Cell wall biogenesis and modification are dependent on vectorial membrane traffic, not only during normal development, but also in stress responses and in plant defence against pathogens and/or symbiosis. It is surprising how little we know about these processes in plants, from small GTPase regulation to the tethering complexes that act as their effectors. Tethering factors are single proteins or protein complexes mediating first contact between the target membrane and arriving membrane vesicles. In this review we focus on the tethering complexes of the best-studied plant model – Arabidopsis thaliana. Genome-based predictions indicate the presence of all major tethering complexes in plants that are known from a hypothetical last eukaryotic common ancestor (LECA). The evolutionary multiplication of paralogs of plant tethering complex subunits has produced the massively expanded EXO70 family, indicating a subfunctionalization of the terminal exocytosis machinery in land plants. Interpretation of loss of function (LOF) mutant phenotypes has to consider that related, yet clearly functionally-specific complexes often share some common core subunits. It is therefore impossible to conclude with clarity which version of the complex is responsible for the phenotypic deviations observed. Experimental interest in the analysis of plant tethering complexes is growing and we hope to contribute with this review by attracting even more attention to this fascinating field of plant cell biology.